Design, Fabrication and Testing of a MnO2 based Catalytic Converter - Albert, JJ; John, Frank; Ronald, Mohit; Arora, Aman; Sharma, Himanshu; Hamilton, Anurag; John Wessley, Jims (International Journal of Computer Sciences and Engineering, 2025)
Millions of people around the world who enjoy the benefits provided by automobiles also suffer the agony of traffic pollution. However, advances in automotive technology are helping to stem the tide of pollution and recent investigations into the success of one specific anti-pollution automotive component has uncovered one of the planet’s greatest environmental success stories which may have global implications as the markets for new cars expand. The device is the catalytic converter, which cleans gases passing through vehicles’ exhaust systems. As exhaust gases passes through the catalysts, the chemical reactions convert the pollutants into harmless gases and water. Hydrocarbons react with oxygen to form carbon dioxide, and oxides of nitrogen react with carbon monoxide to produce nitrogen and carbon dioxide and with hydrogen to produce nitrogen and water vapor. The catalyst, which causes a faster chemical reaction at a lower temperature, is usually a mixture of the noble metals platinum, palladium and rhodium. In the present research a low-cost three-way catalytic converter was developed using MnO2 (Manganese-di-Oxide) as an oxidizing agent in place of CoO (Cobalt Oxide) and testing it on an IC engine. The results obtained from the project will enable commercial application of MnO2 in catalytic converters to reduce the cost as well as eliminate the possible health hazards of CoO which is used in the commercially available catalytic converters at present.